(untitled) (Raparin Journal of Humanities (RJH), 2024)
A dialogue scene in a novel gains a great and effective importance to clarify the human’s psychological needs and instincts. It is the most vital narrative means that the novelist uses to express his/her visions, thought and perspectives through the main and marginal and marginal characters in his/her novel. In this study, it is intended to combine these scenes and their dimensions as an effective method to understand and explore the human psyche through the dialogues of the characters. This may enable the reader to clearly visualize what was going on in Iraqi society during the last decade of the twentieth century and the beginnings of the twenty-first century in light of the accumulated overlap between art and reality in man’s everyday life. Additionally, this study attempts to approach these dimensions in the introduction and four sections distributed among the social, psychological, political, philosophical, appended to the most prominent findings.